2023
DOI: 10.1108/heswbl-02-2023-0044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of an industrial placement year on students' competency development: a three-cohort, longitudinal study

Abstract: PurposeDrawing on human capital theory and sustainable career theory, this paper aims to explore the impact of undertaking an industrial placement on the “Great Eight” competencies as perceived by university students and line managers.Design/methodology/approach618 students and their line managers across three cohorts (pre-COVID-19) took part in a longitudinal quantitative study. Students completed a three-wave questionnaire at the placement's start, middle, and end. Line managers completed the questionnaire d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Additionally, previous studies have focused on how work-integrated learning opportunities can enhance students' PE (e.g. Hughes et al, 2023;Jackson and Dean, 2022) through experiential learning (Kolb, 2015). Our findings emphasise the need for a more holistic approach to learning, embracing lifewide learning opportunities (Cole and Donald, 2022) and highlighting the potential significance of non-traditional forms of learning and development on WB and PE outcomes.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 49%
“…Additionally, previous studies have focused on how work-integrated learning opportunities can enhance students' PE (e.g. Hughes et al, 2023;Jackson and Dean, 2022) through experiential learning (Kolb, 2015). Our findings emphasise the need for a more holistic approach to learning, embracing lifewide learning opportunities (Cole and Donald, 2022) and highlighting the potential significance of non-traditional forms of learning and development on WB and PE outcomes.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 49%
“…Although proficient in offering students foundational learning, traditional educational settings predominantly provide theoretical knowledge (Lantu et al, 2022;ACEN, 2015). It has become essential for students to be equipped with practical skills and attributes sought by employers (Wang et al, 2023;Dean and Rook, 2023;Lim et al, 2023;Hughes et al, 2023;Jackson et al, 2019). Australian universities focus on enhancing employability through practical experiences such as internships and industry placements, integrating WIL in their curricula to provide students with real-world experience and skills (Saito and Pham, 2020).…”
Section: The Role Of Wil In Employability Preparationmentioning
confidence: 99%
“…While in-class simulations enhance career readiness, placements develop relationships between students, organisations and the broader community. These placements empower students to identify opportunities and leverage their intuition, potentially leading to the creation of new ventures (Lantu et al, 2022;Wang et al, 2023) and the development of human capital for both the tertiary institution and the partner organisation (Hughes et al, 2023;Lantu et al, 2022). Petruzziello et al (2024) suggest that students who participate in WIL programs exhibit higher levels of employability due to the practical experience and professional networks they gain.…”
Section: The Role Of Wil In Employability Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Placement graduates are more likely to be in work, find graduate positions more quickly, and earn more than non-placement students (Smith et al, 2018). Through a survey of 618 participants Hughes, Mouratidou and Donald (2023) found that students self-perceived that they improved across eight competencies between the start and end of their placements, a perception confirmed by their placement managers, who rated students' post-placement abilities even higher than the students did. A mixed methods study exploring PhD student expectations concerning employability at a UK Russell Group university found that placements enhanced transferable workplace skills and illuminated a wide range of non-academic employment pathways (Stamati and Willmott, 2022).…”
Section: Introductionmentioning
confidence: 97%